ANALYSIS STUDY OF THE INFLUENCE OF BUILDING MODEL AND FOUNDATION ON LATERAL EARTH PRESSURE DISTRIBUTION ON BASEMENT WALL DUE TO SEISMIC LOAD - Muktadir, Redho
In designing the basement of multi-storey buildings located in earthquake-prone areas, one important aspect that needs to be taken into account is the lateral pressure due to the load on the basement wall. Many factor affect the soil-structure interaction in the design of the basement. These factors include soil condition or site class, basement wall depth, seimic sources and peak base acceleration. In this study variation of soil condition os represented as homogeneous clay based in SNI 2012 with classification of site class as follows SC, SD and SE for stiff clay, firm clay and soft clay. The focus of this research is see the influence of the structure of the building above and the foundation of the basement using finite difference software that is FLAC 2D. Based on the results of the analysis that has been carried out, it can be concluded that the influence of the structure of the building above gives a burden on the basement wall so as to provide perlawana against the lateral pressure that occurs. The effect of the foundation gives stiffness to the structure of the basement. Then the influence of the building structure and foundation in the basement can reduce the value of lateral soil pressure due to earthquake loads